Utilisation Des Caractères Biochimiques, Agronomiques Et Morphologiques Pour L’évaluation De La Diversité Génétique Des Variants D’orangers Dans La Région Du Gharb, Maroc - Yacoubi R.; N. Handaji; N. Arsalane; M. Ibriz; H. Benyahia (European Scientific Journal, ESJ, 2018)
20 clones of orange trees, identified at the level of the collection of nucellar citrus varieties, have been the subject of several tests of behavior at the level of different citrus fruit sites in Morocco. Indeed, the present work aims to evaluate these variants on a clay soil at the Gharb region (INRA/Kenitra). The variants grafted on Citrange troyer were divided into three groups. Each group contains variants, genetically similar, from seedlings of the same parent variety. Clonal selection is based on the synthesis of the results of the study of the variability of the criteria of fruit quality and production. The average yield varies from 44.25 kg / tree to 217.30 kg / tree. While the average weight of a fruit varies from 95 g to 360 g. The results showed a predominance of juicy and medium-sized fruits with an equatorial diameter greater than 56 mm, acceptable for the fresh fruit market or the juice industry. The maturity coefficient study of the variants within each group, or between the three groups, showed that the harvest period extends over four months, from December to March. The final selection was focused on six productive and good quality variants. These promising variants have been described according to UPOV, and then presented for registration in the official catalog.